Near-Approach Imaging Simulation of Low-Altitude ENA Emissions by a LEO Satellite - Lu, Li; Yu, Qing-Long; Lu, Qi (Frontiers in Astronomy and Space Sciences, 2020)
We simulate a 2-D ENA coded modulation imager on board a polar orbit satellite. An imaging measurement, which can realize continuous monitoring of low-altitude ENA emission sources, is applied to the evolution process of energetic ion events. The present simulation results show that: (1) Low earth polar orbit satellites can approach ENA emission sources from inside and outside the inner radiation belt. At low altitude, ENA images can be collected with a time resolution of only 5 seconds, enabling for the first time to observe the evolution process of energetic ion events, on top of determining a global distribution pattern of energetic ions; (2) For tracing energetic particle trigger source of substorm, the propagation distance of energetic particles can be calculated by using time difference of ENA energy spectrum response of different energy channels; (3) Due to the proximity of the ENA emission source, the ENA imager will respond to medium and small-magnitude signals of substorms, which will help sample continuous collection and statistical analysis of massive data under various geomagnetic activities, and provide important data support for space weather forecasts.